Intraspecific genomic divergence and minor structural variations in leishmania (Viannia) panamensis (2020)
Leishmania (Viannia) panamensis is one of the most important Leishmania species associated with cutaneous leishmaniasis (CL) in Latin America. Despite its wide geographic distribution and pathogenic potential in humans and animals, the genomic variability of this species is low compared with other Leishmania species circulating in the same geographical area. No studies have reported a detailed analysis of the whole genome of L. panamensis from clinical isolates using DNA highthroughput sequencing to clarify its intraspecific genomic variability or plausible divergence. Therefore, this study aimed to evaluate the intraspecific genomic variability of L. panamensis from Colombia and Panama. A total of 22 genomes were analyzed, 19 from Colombian patients with CL and three genomes from Panama obtained from public databases. The phylogenomic analysis revealed the potential existence of three well-supported clades as evidence of intraspecific divergence. Additionally, the whole-genome analysis showed low structural variations in terms of ploidy, copy number variations, and single-nucleotide polymorphisms (SNPs). SNPs shared among all clades were identified, revealing their importance in different biological processes of L. panamensis. The findings not only expand our knowledge of intraspecific genomic variability of one of the most important Leishmania species in South America but also highlights the possible existence of different clades/lineages/subpopulations across a geographic scale. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.